Perempuan atau Wanita? Perbandingan Berbasis Korpus tentang Leksikon Berbias Gender - Yuliawati, Susi (Paradigma: Jurnal Kajian Budaya, 2018)
Amidst the debates over the most appropriate Indonesian term for ‘woman’, the present research examines the use of the gendered terms perempuan and wanita. The aim of this research is to reveal which term is more preferable and how the terms are used to talk about women. Using corpus-based approach, this study compared the frequency and pattern of word usage of perempuan and wanita obtained from two corpora, namely IndonesianWac and ind_mixed_2013. The research used a mixed-method design in which quantitative analysis was used to identify word frequency and to measure significant collocation, while qualitative analysis was used to determine meanings on the basis of semantic preference. The study reveals that the term wanita tends to be more frequently used than the term perempuan to signify ‘woman’. In terms of meaning, both terms are used to talk about women in relation to their body (especially their reproductive functions), other people (particularly men), family, and age. The difference is that perempuan tends to be used to talk about women in relation to gender equality and organization, while wanita tends to focus on women’s sexual relationship. Furthermore, results strongly indicate that perempuan tends to denote women in relation to their roles in public domain, whereas wanita tends to denote women in relation to their roles in domestic domain.